Managing the Exit : Lessons from Japan's Reversal of Unconventional Monetary Policy - Syed, Murtaza; Yamaoka, Hiromi (Washington, D.C. : International Monetary Fund, 2010)
In responding to the global crisis, central banks in several advanced economies ventured beyond traditional monetary policy. A variety of unorthodox measures, including purchases of public and private assets, have significantly enlarged their balance sheets. As recoveries take hold, focus will increasingly shift from countering the Great Recession to orchestrating an exit and returning to a more normal monetary framework. Five years ago, as its economy recovered from a severe financial crisis, Japan attempted just such an exit. This note revisits the Bank of Japan's experience and draws potential lessons for managing an orderly exit today, with a focus on technical aspects, practicalities, and communication strategies. While the nature of the assets acquired during the present crisis could pose additional complications, parts of Japan's arsenal-communication, flexibility, a sufficient set of policy tools and a strategy for using them, safeguards against potential losses, the revival of risk appetite through decisive restructuring of balance sheets, and refinements to the monetary framework upon exit-also could be important this time around.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet